2006
DOI: 10.1590/s1516-44462006000100014
|View full text |Cite
|
Sign up to set email alerts
|

Training of evidence-based assessment and intervention approaches in cross-cultural contexts: challenges and solutions

Abstract: Training of evidence-based assessment and intervention approaches in cross-cultural contexts: challenges and solutions Treinamento de estratégias de intervenção e avaliação baseadas em evidências em contextos transculturais: desafios e soluções A b s t r a c t Dissemination of evidence-based assessment and intervention approaches for child and adolescent with behavioral and/or emotional problems is now a priority in the field worldwide. However, developing staff competence in evidence-based assessment and inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 17 publications
(6 reference statements)
0
7
0
Order By: Relevance
“…Furthermore, trainees have specialized cross-cultural psychiatric knowledge and skills, including treatment of refugees and immigrants, socio-cultural variables that influence the assessment and treatment of a wide range of psychiatric conditions, and a comfortable relationship with cultural dynamics that influence both the psychiatrist/patient relationship and collaboration with a wide range of mental health professionals [15,41,60–[62,73,81,89]. A correlation between therapists’ satisfaction with training and consultation, treatment acceptability, and the likelihood to use the treatment in the future was reported [49,103]. Way et al [120] reported a statistically significant increase in communication and interaction, respect for recipients of inpatient care, and increases in cultural competence levels.…”
Section: Recommendationsmentioning
confidence: 99%
“…Furthermore, trainees have specialized cross-cultural psychiatric knowledge and skills, including treatment of refugees and immigrants, socio-cultural variables that influence the assessment and treatment of a wide range of psychiatric conditions, and a comfortable relationship with cultural dynamics that influence both the psychiatrist/patient relationship and collaboration with a wide range of mental health professionals [15,41,60–[62,73,81,89]. A correlation between therapists’ satisfaction with training and consultation, treatment acceptability, and the likelihood to use the treatment in the future was reported [49,103]. Way et al [120] reported a statistically significant increase in communication and interaction, respect for recipients of inpatient care, and increases in cultural competence levels.…”
Section: Recommendationsmentioning
confidence: 99%
“…Six individual barriers across five articles were identified addressing the availability of services. Specifically, lack of professional community-based service providers (Eapen & Ghubash, 2004;Murray et al, 2006), as well as insufficient resources needed to provide the required services (Schwartz, Duvdevany, & Azaiza, 2002;So et al, 2006) were highlighted as factors in the lack of the availability of services.…”
Section: Barriers To Psychosocial Treatment and Service Implementationmentioning
confidence: 99%
“…The interventions were designed to be brief (8–12 sessions) and to address children and parents in schools and clinical settings. The process of developing and implementing these strategies in four different countries has been extensively described elsewhere (Bauermeister, So, Jensen, Krispin, & El Din, 2006; Hoagwood, Kelleher, Murray, & Jensen, 2006; Murray, Fayyad, Jensen, Hoagwood, & Azer, 2006; So et al., 2006) and exemplifies a technique to reach more children over different cultures, and not only the English‐speakers (Jensen, 2006).…”
Section: Evidence‐based Preventive Psychopharmacological and Psychosmentioning
confidence: 99%